Survival of Methanogenic Archaea from Siberian Permafrost under Simulated Martian Thermal Conditions - Morozowa, Daria; Möhlmann, Diedrich; Wagner, Dirk (Origins of Life and Evolution of Biospheres, 2006)
Methanogenic archaea from Siberian permafrost complementary to the already well-studied methanogens from non-permafrost habitats were exposed to simulated Martian conditions. After 22 days of exposure to thermo-physical conditions at Martian low- and mid-latitudes up to 90% of methanogenic archaea from Siberian permafrost survived in pure cultures as well as in environmental samples. In contrast, only 0.3%–5.8% of reference organisms from non-permafrost habitats survived at these conditions. This suggests that methanogens from terrestrial permafrost seem to be remarkably resistant to Martian conditions. Our data also suggest that in scenario of subsurface lithoautotrophic life on Mars, methanogenic archaea from Siberian permafrost could be used as appropriate candidates for the microbial life on Mars.